Singularidades do tipo D(q,p) - Carvalho, Rafaela Soares de [UNESP] (2016)
In this work we study germs of functions under the action of the R_I group of diffeomorphisms of germs in C^n which preserving an ideal I, describing the concepts of codimension and finite determination associated. This provides the tools to characterize a particular type of germ with non isolated singularities, the so called D(q,p) singularities. We can still relate the concept of R_I-stability with these germs, in the case where I is a radical ideal that defines complete intersection with isolated singularity. Moreover, we present a coordinate system by which we obtain an explicit formula for some Lê numbers of these germs.